A Reader's guide to Canadian history. - Muise, D. A. (Delphin Andrew), 1941- (Heritage., 1982)
Six experts guide the reader through the maze of historical writing about pre-Confederation Canada with a critical assessment of the best and most useful articles, papers, and books that have been published.